Evaluation of Knowledge Levels of Dentistry Students on the COVID-19 and its Effects on Depression - Esra Kızılcı; Cansu Demiroğlu; Burcu Duman; Hüsniye Gümüş (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the level of knowledge of dentistry students regarding the COVID-19 outbreak and to evaluate whether the risk factors of the outbreak cause depression. Material and Methods: This study was conducted with 516 dentistry students (3rd, 4th and 5th grades) who started clinical practice in their education. The first part of the questionnaires applied to the students includes questions about demographic information, while the second part contains questions to determine their knowledge levels on the COVID-19 pandemic and protection against it.  In the third section, Beck Depression Inventory (BDI) was used to examine depression symptoms. The data were analyzed by frequency analyses and Chi-squared tests via the IBM SPSS 22.0 software. Results: Of the 516 students, 150 (29%) participants were in the 3rd, 212 (41%) were in the 4th and 154 (30%) were in the 5th grade. 355 (69%) students stated that their knowledge level about COVID-19 was high. 30.9% were conscious of the importance of using masks. 29.6% were aware of the importance of using gloves, 30.3% of not shaking hands. According to BDI scores, 37.1% of the participants seemed to experience moderate to severe and very severe depression. Conclusion: It was observed that the students didn't have a sufficient level of knowledge about the factors affecting the spread of the pandemic. New stress factors such as COVID-19 may increase the incidence of depression.